A name and subject index to the World War II documents on the Panay guerilla resistance movement at the Central Philippine University Library - Lopez, Perla H. (1978)
The Central Philippine University collection of World War II documents on the Panay resistance movement consists of almost 217 bound volumes of unsorted documents compiled and bound as they were acquired by the library. These documents include circulars, directives, orders, proclamations, letters, etc. issued by leaders of the armed guerrilla units or those of the civil resistance underground movement, during the darkest days of the Japanese years from 1942 to 1945. Although the arrangement of the documents by volumes presupposes an order that would render location of the documents relatively easier then when these documents are just filed in a tumbled fashion, nevertheless this arrangement still presents a searching and retrieval problem especially when there is no idea in which particular volume some needed information can be found. Searching into this vast collection of unclassified documents requires some tools which would guide researchers in locating the information they need. One of the tools which facilitates document research is the index.